Evasive invasives? Implications of neophobia for feral cat (Felis catus) control - Ned L. Ryan‐Schofield; John L. Read; Hugh W. McGregor; Todd J. McWhorter; Katherine E. Moseby (Wildlife Society Bulletin)
Abstract Neophobia is an ecologically relevant personality trait that manifests as aversion to new or unfamiliar stimuli. Fear and subsequent avoidance of novel stimuli represents a challenge for pest management programs, as control tools that induce a neophobic response will reduce their effectiveness. Additionally, neophobia can be a plastic trait induced by exposure to high‐risk environments, and so can be exacerbated by repeated harassment, which often occurs in pest management programs that are conducted at high intensity. We investigated the propensity of feral cats (Felis catus) to exhibit neophobic behavior towards a novel control device. We also tested whether neophobia was altered by capture and radio‐collaring or changed over time. We found that there is significant potential for initial avoidance of control devices by some feral cats, and that capture and handling significantly increased the likelihood of avoidance. Neophobia generally declined over time suggesting that long‐term deployment may reduce the impact of neophobia. Avoidance of novel control tools could severely limit their effectiveness, especially if deployed to remove the last remaining cats from confined areas. Remaining cats may have avoided repeated attempts at conventional control techniques and so may be more neophobic. In such circumstances, control tool deployments should be lengthened considerably, to take advantage of waning neophobia over time, and, concealed effectively to hide them from neophobic cats. The increased neophobia recorded in cats that were handled and radio‐collared for monitoring suggests that results from experiments that test new control devices may not be indicative of the behavior of naïve cats. Changes to methodology such as minimizing capture and handling may be required to reduce neophobia and provide valid research results when testing novel control tools.